2019
DOI: 10.32948/auo.2019.03.28
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs and Its Implication as Biomarkers in Renal Cell Carcinoma: A Systematic Analysis

Abstract: Renal cell carcinoma (RCC) is one of the most devastating disease with higher mortality rates. It comprises several subtypes exhibiting distinct histological features and clinical staging. Despite recent advancement in understanding the biology of RCC success in treatment rates remains dismal. This may be partly due to lack of specific biomarkers for early detection/prognosis and poor clinical outcome. Noncoding protein transcripts in the genome play important role in the initiation, evolution and progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Recent study has indicated dysregulation of circRNAs in ccRCC and the association of circRNAs with malignant behavior in ccRCC . Hsa_circ_0001451 was downregulated in ccRCC tissues and correlated with the clinicopathological features and OS of ccRCC patients .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent study has indicated dysregulation of circRNAs in ccRCC and the association of circRNAs with malignant behavior in ccRCC . Hsa_circ_0001451 was downregulated in ccRCC tissues and correlated with the clinicopathological features and OS of ccRCC patients .…”
Section: Discussionmentioning
confidence: 92%
“…Circ‐ABCB10 overexpression or hsa_circ_0001451 knockdown promoted ccRCC proliferation and induced cell apoptosis in vitro, revealing the relationship between potential markers and therapeutic targets of circRNAs in ccRCC. Additionally, increasing evidence has shown the functional roles of circRNAs as promoters or inhibitors of cancer‐critical genes of ccRCC, thus involved in the regulation of tumor progression . circATP2B1 promoted ccRCC invasion through miR‐204‐3p‐mediated fibronectin 1 expression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation